Scientific and Digital Literacy Profiles of Biology Education Students across Semester Levels in Higher Education in Sulawesi - Nurul Fadhilah; Adnan Adnan; Yusminah Hala; Andi Faridah Arsal; Andi Asmawati Aziz; Ismail Ismail (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Digital-based biology learning requires prospective biology teachers to have integrated scientific and digital literacy, but the profiles of both across semester levels remain limited. This study aimed to map the scientific and digital literacy profiles of biology education students from higher education in Sulawesi based on semester level. A quantitative survey design was employed involving 394 undergraduate biology education students from semesters II, IV, VI, and VIII. Data were collected using questionnaires adapted from the OECD/PISA scientific literacy framework and DigComp 2.2 digital competence framework. The data were analyzed using descriptive statistics, one-way anova, and tukey HSD post hoc tests. The results showed that scientific literacy increased from semesters II to VIII, with all groups classified in the high category. Digital literacy also increased descriptively, with semester VIII students reaching the very high category. Anova results indicated a significant difference in scientific literacy based on semester level, F(3.390) = 4.470, p = 0.004, whereas digital literacy did not differ significantly, F(3.390) = 2.507, p = 0.059. The tukey HSD test showed that a significant difference in scientific literacy occurred only between students in semester II and VIII. These findings indicate that scientific literacy develops cumulatively through academic progression, whereas digital literacy is relatively evenly distributed across semesters. The study highlights the need to integrate scientific inquiry, evidence evaluation, data interpretation, and critical digital competence into biology education curriculum.